Amiodarone-Related Pure Red Cell Aplastic Anemia and Hypothyroidism in a Child With Total Anomalous Pulmonary Venous Connection - Ba, Hongjun; Xu, Lingling; Peng, Huimin; Li, Xuandi; Lin, Yuese; Wang, Huishen; Qin, Youzhen (Frontiers in Pediatrics, 2019)
Amiodarone is an effective anti-arrhythmic drug, but there are many clinical side effects that limit its application. There are no case reports of amiodarone-related pure red cell aplastic anemia (PRCA). Here, we present a case of amiodarone-related PRCA and hypothyroidism in a 7-month-old boy. The patient had complete anomalous pulmonary venous drainage (intracardiac type) and had undergone cardiac surgery at the age of 2 months. Eleven days after the operation, atrial tachycardia was observed. Amiodarone was administered orally (15 mg/kg.d), following which the arrhythmia was under control. Subsequently, the patient was prescribed amiodarone (5 mg/kg.d) and discharged. Regular medical consultations were not conducted as required. At 7 months of age (5 months after the operation), the patient returned to the hospital for re-examination. The electrocardiogram showed intermittent sinus bradycardia, occasional junctional escape, hemoglobin 79 g/L, and thyroid function – TSH 9.660 uIU/mL. Amiodarone was discontinued. Thyroxine was given orally. Subsequently, the heart rate improved and TSH returned to normal levels. Nutritional therapy was recommended based on a diagnosis of nutrition-related anemia. A re-visit at 9 months of age showed that the weight was 6 kg, but the routine blood test indicated that hemoglobin was 59 g/L with positive cell anemia and low reticulocyte count. Bone marrow cytology examination suggested PRCA. The hemoglobin level was gradually restored after treatment with prednisone. The use of amiodarone in small infants and young children and its side effects should be carefully monitored. The potential mechanism of amiodarone-related PRCA needs further study.